IMPLIKASI HUKUM INTERNASIONAL TERHADAP PEMUNGUTAN SUARA SISTEM NOKEN/IKAT DI PAPUA - Yusty Foxdey Rahawarin (Fakultas Hukum, Universitas Caritas Indonesia, 2025)
The Noken/Ikat voting system reflects a recognition of Papuan traditions. This is important for maintaining cultural identity, but it needs to be aligned with appropriate legal regulations. The author uses a normative juridical approach, examining the application of rules or norms in positive law. The results of this paper: Voting using the Noken system has been legitimized by the Constitutional Court (MK) in Case Number 47-81/PHPU. A-VII/2009, which was then reinforced by regulations issued by the General Elections Commission (KPU), namely, General Elections Commission Decree Number 216 of 2024 concerning Amendments to General Elections Commission Decree Number 66 of 2024 concerning Technical Guidelines for the Implementation of Voting and Vote Counting in General Elections. Based on these regulations, the Noken/Ikat system is the result of